2022
DOI: 10.1088/1361-6463/ac7e08
|View full text |Cite
|
Sign up to set email alerts
|

Photonic spin Hall effect in symmetrical structure containing Dirac semimetal materials

Abstract: Dirac semimetal, called three-dimensional graphene, has attraction wide attraction with its adjustable thickness and Fermi energy. However, the performance of photonic spin Hall effect with Dirac semimetal is still unknown. In this work, we establish a symmetrical structure composed of glass prism, three-dimensional Dirac semimetal (3DDS) and Si to study the dependence of spin shift on the thickness and Fermi energy of 3DDS. We find that the magnitude and the position of the spin shift can be controlled by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…For example, Yin et al discussed the enhanced PSHE in a Bragg reflector consisting of 3DDS, a space layer, and a onedimensional photonic crystal, which was caused by the excitation of the optical Tamm states [22]. Song et al proposed a symmetrical structure containing 3DDS and found that this structure also supports the enhanced PSHE because of the excitation of the surface plasmon resonance in the 3DDS material [23]. In addition, both of the magnitudes of their spin shifts can be controlled by the Fermi energy of 3DDS.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yin et al discussed the enhanced PSHE in a Bragg reflector consisting of 3DDS, a space layer, and a onedimensional photonic crystal, which was caused by the excitation of the optical Tamm states [22]. Song et al proposed a symmetrical structure containing 3DDS and found that this structure also supports the enhanced PSHE because of the excitation of the surface plasmon resonance in the 3DDS material [23]. In addition, both of the magnitudes of their spin shifts can be controlled by the Fermi energy of 3DDS.…”
Section: Introductionmentioning
confidence: 99%